THE IMPORTANCE OF CONFORMISM IN PREVENTING FAMILY VIOLENCE IN UZBEKISTAN (Scientific journal of the Fergana State University, 2026)
This article scientifically analyzes the factors of origin of repression and violence in family relationships and the positive and negative aspects of the conformism factor in their prevention. The study reveals the Social, Psychological and cultural foundations of domestic violence, highlighting gender stereotypes and the impact of the social environment in this process. The activities of regulatory legal acts, state programs and rehabilitation and social adaptation centers aimed at protecting women from harassment and violence have also been analyzed in Uzbekistan. In addition to the positive aspects of the conformism factor in ensuring social stability in family relationships, the negative aspects that serve to hide and perpetuate violence are also justified.